Experiencing studying in a phenomenographic analysis of the utterances of young adults from Z-Generation - Jurgiel-Aleksander, Alicja; Aleksander, Zdzisław (Rocznik andragogiczny, 2025)
The aim of this article is to present the results of an analysis of indepth phenomenographic interviews conducted with young adults studying the humanities and social sciences in the Polish higher education system. The authors conducted twenty interviews in 2022 and 2023 with individuals who represented the next generation of university students in their families, focusing on their experiences of studying. The authors conceptualise these experiences from the perspective of representatives of Generation Z in the following ways: (a) as a transition to the next stage in the formal education system, leading to the acquisition of higher qualifications; (b) as a learning process for acquiring and deepening knowledge; (c) as a life stage characterised by the absence of parental care; (d) as the assumption of the student role associated with belonging to an institution such as a university; and (e) as building relationships within and outside university. The authors interpret the identified categories of description as follows: as a consequence of the popularisation of the educational process and its normalisation in everyday life; as a result of students’ intrinsic motivation, derived from cultural capital and aligned with the perception of knowledge acquisition as a developmental process; as an outcome of limited opportunities to practice social competencies in earlier stages of schooling; and as an effect of rapid civilisa Celem niniejszego artykułu jest przedstawienie wyników analizy pogłębionych wywiadów fenomenograficznych przeprowadzonych wśród młodych dorosłych studiujących w polskim systemie edukacyjnym na wyższych uczelniach humanistykę i nauki społeczne. Autorzy przeprowadzili w latach 2022 i 2023 dwadzieścia wywiadów na temat doświadczania studiowania z osobami, które są kolejnym pokoleniem studiującym w swoich rodzinach. Konceptualizacje owego doświadczenia w ujęciu reprezentantów pokolenia Z autorzy widzą w następujących formach: (a) jako wejście na kolejny etap w systemie kształcenia formalnego prowadzący do zdobycia wyższych kwalifikacji, (b) jako proces uczenia się prowadzący do zdobycia nowej wiedzy i jej pogłębiania, (c) jako etap w życiu bez rodzicielskiej opieki, (d) jako wchodzenie w rolę studenta związaną z przynależnością do instytucji, jaką jest uczelnia, (e) jako budowanie relacji na uczelni i poza nią. Wyodrębnione kategorie opisu autorzy widzą kolejno jako: konsekwencję upowszechnienia procesu kształcenia, a tym samym jego naturalizację w codzienności; rezultat wewnętrznej motywacji studentów wynikający z kapitału kulturowego, rezonujący z postrzeganiem zdobywania wiedzy jako procesu rozwojowego; skutek deficytu w praktykowaniu społecznych kompetencji na wcześniejszych etapach szkolnej edukacji; następstwo cywilizacyjnego i technologicznego przyspieszenia oraz pokłosie indywidualnej potrzeby upodmiotowienia procesu uczenia się. Ujawnione w ten sposób kwestie edukacyjne stanowią zapowiedź dalszych studiów i interpretacji wyników tego projektu, jak przystało na fenomenografię, w kulturowym kontekście